The state of climate negotiations - Brian P. Flannery (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
Today, with little time remaining, negotiators confront a disorganized text that is far too long and replete with conflicting proposals that cross red lines for major players. Nonetheless, political leaders express confidence that a deal is achievable.Unlike the task of Kyoto—producing politically feasible mitigation targets for developed nations—the post 2020 agreement covers (at least) six themes: mitigation for all nations, adaptation, finance, technology transfer, capacity building and transparency. Residual acrimony and distrust from Copenhagen hamper the process which must resolve many complex, contentious issues, e.g. legal form and compliance, the role (or not) for markets and offset projects, intellectual property rights, compensation for loss and damage, transparency and associated measurement, reporting and verification (MRV) and review procedures. Overshadowing all remains the question of how the principle of common but differentiated responsibilities (CBDR) will manifest throughout the agreement, e.g. from mitigation to reporting and review to finance.Some aspects are solidifying. Mitigation efforts will not be negotiated; rather, they are being submitted (as Intended Nationally Determined Contributions: INDCs), and, ultimately, recorded, perhaps (dropping the I) becoming NDCs. Total financial aid appears set by the Copenhagen pledge of developed nations to mobilize 100 billion US per year by 2020. Also, negotiators appear resolved to create a durable framework based on cycles of review and renewal over intervals of, perhaps, 5 or 10 years.However, the Paris Agreement appears unlikely to fulfill the long-established narrative to be "on track" to limit warming to less than 2 (or 1.5) C. Only recently have political leaders begun to temper expectations. They will need to manage expectations thoughtfully to avoid a backlash from a range of nations, stakeholders and media, and to restore the credibility of United Nations Framework Convention on Climate Change (UNFCCC) as an effective process.
Keywords: 330